Towards determining the dietary lysine requirement in the South African abalone, Haliotis midae - Lloyd, Kyle Everett (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2016)
Animals generally do not have a requirement for protein, but instead have a requirement for specific essential amino acids (EAAs) and non-essential amino acids (NEAAs). The NEAAs are those that can be synthesised by the animal, however, EAAs cannot be synthesised and must therefore be supplied as part of the diet. When these amino acids (AAs) are supplied in the correct ratios and with the correct level of digestible energy, nutritionists can maximise somatic growth from proteins. This has resulted in increased research into the use of crystalline AAs as a tool in feed formulation research in order to quantify the AA requirements in aquaculture species, and allow for alternative protein sources (other than fishmeal) to be utilised. In common with other water soluble nutrients, leaching of crystalline AAs from diets prior to ingestion is of concern in an aquatic environment. Microencapsulation techniques have been successfully employed to restrict micronutrient leaching, and improve ingestion rates. In this research, LysiPEARL™ (Kemin®) was used as a means to determine the lysine requirement in Haliotis. midae. This encapsulated lysine product is used in the dairy cattle industry as an effective source of rumen bypass for intestinal release of lysine. It has previously been proposed that crystalline AAs are not suitable for AA studies in H. midae due to the slow feeding rates of the species as well as the solubility of these AAs. However, 90.00 % of supplemented lysine was maintained in this study after a six hour period of leaching, showing that if effective microencapsulation techniques are used, it is possible to use crystalline amino acids to supplement protein bound lysine in abalone feeds. Six isoenergetic (15.90 MJ/kg), isolipidic (6.00 %) and isonitrogenous (29.00 %) diets enriched with 5.52, 6.40, 7.28, 8.14, 9.00 and 9.86 % lysine (as a % of protein) were fed to triplicate groups of 20 H. midae (20.41 ± 1.95 mm SL 1.51 ± 0.44 g w.wt) for 90 days. Wet weight and shell length measurements were taken every 30 days and specific growth rate (SGR) (% body weight.day-1), feed conversion ratio (FCR), protein efficiency ratio (PER), feed consumption (% body weight.day-1) and condition factor were calculated for each dietary treatment. Linear regression showed that FCR increased as dietary lysine increased (Regression analysis, p=0.031), and that PER reduced as dietary lysine increased (Regression analysis, p=0.026). Feed consumption also increased as dietary lysine increased (Regression analysis, p<0.001). The inclusion of lysine at 7.28 % of the total protein in the diet resulted in significantly superior SGR (0.57±0.01 % body weight.day-1) to that of 5.52 % (0.42±0.05 % body weight.day-1), FCR (1.51±0.05) to that of 8.14 % (1.99±0.21) and PER (2.45±0.07) to that of 8.14 % (1.99±0.18; ANOVA, p<0.05). There was a significant difference found in feed consumption (% body wt.d-1), with consumption increasing significantly between the first three dietary treatments and the last three dietary treatments (ANOVA, p<0.001). There was no significant improvement in SGR when dietary lysine increased above 7.28 % of the dietary protein in the diet, indicating that dietary lysine requirement was being met at 7.28 %, after which excess lysine promoted no growth response. The diet producing the best SGR, PER and FCR in this study was diet 3 which had a measured lysine content of 6.90 %. The results of the present study suggest that the lysine requirement in H. midae is in the range of 6.00 - 7.00 % of dietary protein. From these data amino acid ratios were used to estimate optimum inclusion levels of other essential amino acids. However, lysine availability in LysiPEARL™ may have resulted in over estimations due to the lipid encapsulation technique used, and haliotids limited ability to efficiently digest lipids. For this reason EAA requirements were suggested based on three different hypothetical scenarios of lysine availability from LysiPEARL™.
Keywords: Uncatalogued